Determinants and outcomes of pathological internet use (PIU) among urban Klang Valley millennial teens / Pressca Neging - Neging, Pressca (2015)
The rapid adoption of Internet has turned the Millennial Teens’ life like a lightning speed. Empirical evidence has illustrated that Pathological Internet Use (PIU) among them ensure long-term success to the market players in the children industry. However, it creates concerns among their care takers as it generates mental disorder among some of them. The purpose of this thesis is to study the determinants of pathological Internet use (PIU) among Millennial Teens in urban Klang Valley in Malaysia and the outcomes of this disorder on their cognitive and behavioral skills, as well as the influence by their personality. A modified Media System Dependency (MSD) model comprising social system, media system, personality system, online consumer self-efficacy and Internet maven are proposed. To the best knowledge of the researcher, there has been no study conducted to date on MSD which integrates personality system in its micro-level relationship. The sample of this thesis consisted of 656 school students between the ages of 16 - 17 year-old sampled in a multi-stage cluster in Malaysia. Exploratory factor analysis was used to extract determinants of PIU. It was found that personality system which consisted of neuroticism trait formed the highest contribution of PIU among Millennial Teens in urban Klang Valley and social system which was made of parents and peers had negative relationship with PIU. Structural Equation Modeling was used to test the study hypotheses. According to the findings, Millennial Teens long time online increased their online consumer self-efficacy and Internet maven skills. Implications for families, research, theory, policy, and education are discussed.